The temporal complexity of international student mobilities - Sergei Shubin (Timespace and international migration, 2017)
This chapter explores the links between migration, temporality and subjectivity, and provides a critical analysis of the standard treatment of time in the study of international student mobility, which is usually understood in terms of maximising utility in the future by moving across a measurable grid of time and space in the present. In contrast, this chapter seeks out the complex, unexpected and ineffable experiences of temporality among young people on the move. Building their argument from Heidegger’s Being and Time, Collins and Shubin seek to move beyond linear and compartmentalised accounts of time by claiming that human being is constituted by different temporalities simultaneously. Such an examination draws out the temporal complexity whereupon age/life stage, mobility and the development of skills and competences are all seen in a broader focus and in coexistence with futures, pasts and presents of migrants. In this framing the authors highlight a discussion that moves beyond the principles of utility maximisation in which students are perceived to be undertaking journeys with the goal of achieving strategic objectives.